Interactions between perceived exertion and thermal perception in the heat in endurance athletes. (August 2018) - Roussey, Gilles; Gruet, Mathieu; Vercruyssen, Fabrice; Louis, Julien; Vallier, Jean-Marc; Bernard, Thierry
Abstract: Introduction: The study aimed to investigate how a distortion of perceived exertion in the heat may affect, during a self-paced cycling exercise preceded by prior cognitive task, the thermal perception and the subsequent regulation of power output in high level athletes. Methods: Eleven endurance trained male athletes completed four experimental sessions including a 30-min fixed-RPE (15-Hard) cycling exercise in neutral (TMP-22 °C) and hot (HOT-37 °C) conditions, following a 60-min incongruent Stroop task (EXP) or passively watching documentary films (CON). Central and peripheral performances of the knee extensors were assessed before the cognitive task and after the exercise. Results: Although mental demand and effort were higher in EXP ( P < 0.05), no effect of prior cognitive task was observed on subjective feelings of mental fatigue or decline in power output at a fixed RPE. Average exercise intensity was lower in HOT than TMP (3.14 ± 0.09 W⋅kg −1 vs. 3.42 ± 0.10 W⋅kg −1 respectively, P < 0.05). Skin temperature and warmth sensations were higher in HOT throughout the exercise ( P < 0.05) but not thermal comfort. Central and peripheral parameters were not affected more in HOT than in TMP. Conclusion: Although the effects of combined stressors on the distortion of perceived exertion could not be verified, the greater decline in power output recorded in HOT than TMP suggest a high contribution of both perceptual and cardiovascular responses in the regulation of work rate when the subject is in mild hyperthermia. Highlights: Prior cognitive task did not induce higher mental fatigue in endurance athletes. Central fatigue did not explain higher decline of power output in the heat. Cutaneous thermal afferents may influence perception of effort in mild hyperthermia. Training level may influence the contribution of thermal strain on perceived effort.